Cadence as a Metaphor of Instability and Conclusive Unity: A Brief Excursus Between Grammar and Music - Iafelice, Carlos Cascarelli [UNESP] (Assoc Nac Pesquisa & Pos-graduacao & Musica, 2019)
The structural development of what we understand as cadence has a long and complex history associated with an awareness and appreciation of musical elements assimilated by a decodification process that is related to adapted morphology. Thus, the connection between music and text goes beyond its joint praxis: it lends structural elements from its main vehicle (text), engendering a true corpus grammaticae musicae. In general terms, this principle resulted in parameters from both synchronic and diachronic dimensions, i.e., a specific set of intervals with a particular melodic progression. The argument presented in this study aims to exam the musical treatises through the end of the fifteenth century in testimonies that contain evidence that corroborate a probable dichotomy between understanding of cadence as a metaphor of instability and conclusive unity.
Keywords: History of music theory; theory of cadence; music grammar; 15th-century music theory